Portrait of the student as a young writer: some student survey findings about attitudes to writing and self‐efficacy as writers. (24th January 2019) - Gadd, Murray; Parr, Judy M.; Robertson, James; Carran, Lliam; Ali, Zeba; Gendall, Linda; Watson, Kate
Abstract: This New Zealand‐based article reports on an analysis of data gathered over two years from upper primary school students on their attitudes to writing and writing instruction and their beliefs about their self‐efficacy as developing writers. Responses from 449 students in five diverse schools are included. Through an online survey administered at the beginning and end of each of the two years, students responded to a range of mostly closed questions. Conclusions (including student comments) were made about students' likes, dislikes and preferences as developing writers. Levels of association between their attitudes and gender and between their attitudes and proficiency levels were explored. Conclusions were also made about how student attitudes affect teacher practice.